Aprendizajes significativos mediante material concreto y aula virtual en el laboratorio de matemática para la sección básica superior - Gavilánez Montero, Aída Janeth (2015)
This research work is located within a viable project, as is the development of a proposal to innovate, strengthen and give the student alternatives to achieve meaningful learning in the explanation and understanding of mathematics. From this perspective, and assuming that the role of a teacher is to be a designer and creator of his own teaching materials, we developed our thesis entitled "SIGNIFICANT LEARNING THROUGH CONCRETE MATERIAL AND VIRTUAL CLASSROOM MATHEMATICS LABORATORY FOR THE UPPER BASIC LEVEL". Some theories and methodologies are included in this work as well as issues relating to holistic education, meaningful learning, and mathematics. The use of Information and communications technology (ICT), etc. Among other key issues. We start with a diagnostic stage of the current situation of the UES "Cardinal Spellman". We support it with tables, statistical charts and triangulation of results from surveys and interviews conducted in that institution. Also, we discuss other educational proposals for the explanation and understanding of mathematics existing in the educational environment. With all the obtained information, the analysis and interpretation of the different themes of the subject, allowed us to develop a Laboratory Training Manual for Mathematics. In this, the explanation and understanding of mathematical concepts using concrete materials and virtual classrooms are presented to improve meaningful learning in students from the upper basic level. We believe that the benefits of this work are for the entire educational community. Because we are providing active methodologies based on the use of particular materials, virtual classroom and basic inputs to achieve empathy within the subject and the significant learning in the classroom, so students will assimilate more easily the contents of the subject, considering that games in general are the foundation to develop the knowledge, and that they are a valid educative tool in our present day.